Enfoque clínico de las relaciones entre salud y trabajo : contribuciones y desafíos - Andrea Pujol; María Inés Gutiérrez (Universidade do Porto, 2019)
The paper briefly reconstructs the perspectives of approach to the relationship between health and work that contribute to understanding the problem of occupational health in Argentina. In the discussion, their main assumptions and orientations are considered in a stylized way ; subsequently, contributions from the work clinic are considered, discussing some principles that guide these interventions, their scope and challenges. The analysis is positioned in the work clinic -which is just emergent in Argentina- highlighting the contributions that differentiate it from predominant approaches, both at the basic proposals and at its methodological derivations. As a closing, some challenges of the work clinic in our disciplinary field are outlined ; if assumed, they will enrich the debates and current practices of psychology about the tensions that are finding expression in the health area at current work scenarios.